1972
DOI: 10.1037/h0032615
|View full text |Cite
|
Sign up to set email alerts
|

A-B therapist distinction, patient diagnosis, and outcome of brief psychotherapy in a college clinic.

Abstract: Prior clinical studies have suggested that therapists' A-B status interacts with patient diagnosis in determining the outcome of psychotherapy (A > B with schizophrenics; B > A with neurotics), but this interaction hypothesis has been studied almost exclusively in laboratory analogues, not in actual clinical practice. To discern whether the hypothesis would apply to brief psychotherapy in a college clinic, the "outcomes" obtained by three A and three B therapists with their schizoid and neurotic patients (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1974
1974
1983
1983

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…As a result of the A-B scores attained by the interviewees, most of them would be considered As, using both the norms developed by Berzins (in 1972) on male students and professionals and the distributions of scores for policemen found in the current study. Although such norms are obviously not directly applicable to this study's interviewee Ss, it would still suggest a greater tendency toward A than B status in the present Ss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the A-B scores attained by the interviewees, most of them would be considered As, using both the norms developed by Berzins (in 1972) on male students and professionals and the distributions of scores for policemen found in the current study. Although such norms are obviously not directly applicable to this study's interviewee Ss, it would still suggest a greater tendency toward A than B status in the present Ss.…”
Section: Discussionmentioning
confidence: 99%
“…** The earliest work demonstrated the increased effectiveness of A-type therapists with schizophrenic patients (Whitehorn & Betz, 1954), and of B-type therapists with neurotic patients (McNair, Callahan, & Lorr, 1962). Later analogue and therapy studies have generalized the earlier findings and suggested the relative superiority of As with schizoid and extropunitive individuals (Berzins, Ross, & Friedman, 1972;Berzins, Seidman, & Welch, 1970) and of Bs with intropunitive individuals . In studies by Carson, Harden, and Shows (1964) and Berzins, Ross, and Cohen (1970), work further removed from the original outcome studies has focused on the process involved and has demonstrated the greater effectiveness of As in eliciting personal information from distrustful subjects.…”
mentioning
confidence: 92%
“…Taken together, the original clinical findings of Betz (1%7) and McNair et al (1%2) gave rise to the hypothesis that therapists characterized by a disinterest in selected manual, technical, or mechanical activities (As) were more clinically successful with schizophrenic patients, and less clinically successful with neurotic patients, than were therapists who indicated an interest in these activities (Bs). Due to the shortage of clinical outcome studies with the requisite factorial design, this ' A-B interaction hypothesis ' has not been fully evaluated, (for reviews see Razin, 1971; Chartier, 1974; May, 1974; Goodwin, 1974), with some indications that such differences as exist primarily concern schizophrenic rather than neurotic patients (Berzins et al, 1972 b;Chartier, 1974). Differences in clinical style have been posited to account for the differential effectiveness of A and B therapists with schizophrenic patients.…”
Section: Clinical Responses Of a And B Practising Psychotherapists Tomentioning
confidence: 99%
“…Moreover, the impact of level of psychotherapy experience on A-B interaction phenomena has never been systematically assessed, despite a growing body of empirical evidence indicating its general importance in relation to process and outcome (e.g. Meltzoff & Kornreich, 1970; Hill, 1975) as well as scattered suggestions that it may qualify A-B phenomena (Kemp, 1%9;Berzins et al, 1971;Hill, 1975).…”
Section: William B Goodwin Jesse D Geller and Donald M Quinlanmentioning
confidence: 99%
“…In order to evaluate the interaction hypothesis in an actual clinical setting as opposed to an analog, laboratory situation, Berzins, Ross, and Friedman (1972) tested the hypothesis in the context of short-term therapy in a college clinic with A and B therapists working with neurotic and schizoid (substituted for schizophrenic) clients. Three factors extracted from ratings completed by clients and therapists were used to evaluate the effectiveness of the therapy: (1) therapists' appraisal of his/her own effectiveness, (2) patient improvement, and (3) patientexperienced rapport.…”
Section: Behavior During Therapy: Tests Of the Interaction Hypothesismentioning
confidence: 99%